Solvent effects in integrated reaction-separation process of liquid-phase hydrogenation of furfural to furfuryl alcohol over CuAl2O4 catalysts - Sutarat Thongratkaew; Sirapassorn Kiatphuengporn; Anchalee Junkaew; Sanchai Kuboon; Narong Chanlek; Anusorn Seubsai; Bunyarat Rungtaweevoranit; Kajornsak Faungnawakij (Catalysis Communications, 2022)
Selective hydrogenation of furfural to furfuryl alcohol over CuAl2O4 catalysts is studied in a batch reactor using a range of solvents of varying chemical properties. We find that the reactions in branched alcohols provide higher furfuryl alcohol yields compared to linear alcohols. Besides, the reactions performed in nonane and decane provide excellent furfuryl alcohol yields of 96%. In situ FTIR analysis indicates that the carbonyl group of furfural is preferentially adsorbed leading to such high catalyst performance. Importantly, the efficient production of furfuryl alcohol in immiscible solvents minimizing downstream process is achieved in this integrative reaction-separation concept.